Optimization of 3D-Visualization of Micro-Anatomical Structures of the Human Inner Ear in Osmium Tetroxide Contrast Enhanced Micro-CT Scans - van den Boogert, Thomas; van Hoof, Marc; Handschuh, Stephan; Glueckert, Rudolf; Guinand, Nils; Guyot, Jean-Philippe; Kingma, Herman; Perez-Fornos, Angelica; Seppen, Bart; Johnson Chacko, Lejo; Schrott-Fischer, Anneliese; van de Berg, Raymond (Frontiers in Neuroanatomy, 2018)
Introduction: Knowledge of the neuro-anatomical architecture of the inner ear contributes to the improvement and development of cochlear and vestibular implants. The present knowledge is mainly based on two-dimensional images (histology) or derived models that simplify the complexity of this architecture. This study investigated the feasibility of visualizing relevant neuro-anatomical structures of the inner ear in a dynamic three-dimensional reproduction, using a combination of staining, micro-CT imaging and an image processing algorithm. Methods: Four fresh cadaveric temporal bones were postfixed with osmium tetroxide (OsO4) and decalcified with EDTA. Micro-CT was used for scanning at 10 μm (4 scans) and 5.5 μm (1 scan) voxel resolution. A new image processing algorithm was developed and the scans were visualized in open source software. Results: OsO4 enhanced the contrast in all scans and the visualization was substantially improved by the image processing algorithm. The three-dimensional renderings provided detailed visualization of the whole inner ear. Details were visible up to the size of individual neurons, nerve crossings and the specific neuro-anatomical structures such as the tunnel of Corti. Conclusion: The combination of OsO4, micro-CT and the proposed image processing algorithm provides an accurate and detailed visualization of the three-dimensional micro-anatomy of the human inner ear.